Evaluation of chemokines CXCL8 and CCL2, serotonin, and vascular endothelial growth factor serum concentrations in healthy dogs from seven breeds with variable predisposition for canine idiopathic pulmonary fibrosis. (August 2015) - Roels, E.; Krafft, E.; Antoine, N.; Farnir, F.; Laurila, H.P.; Holopainen, S.; Rajamäki, M.M.; Clercx, C.
Abstract: The West Highland white terrier (WHWT) is particularly prone to canine idiopathic pulmonary fibrosis (CIPF). We hypothesized that higher circulating concentrations of chemokines CXCL8, CCL2, serotonin (5-HT), or vascular endothelial growth factor (VEGF) could serve as predisposing factors for CIPF development in the WHWT breed. Serum samples from 103 healthy dogs of seven different breeds variably predisposed to CIPF were collected. Serum CXCL8 concentrations were higher in healthy WHWT compared with each of the other groups of healthy dogs. Serum CCL2 concentrations were higher in healthy WHWT and Maltese compared with King Charles spaniels and Malinois Belgian shepherds. No relevant inter-breed differences were observed for serum 5-HT concentrations regarding CIPF predisposition. VEGF values from 89.3% of samples tested were below the kit detection limit. In conclusion, high CXCL8 blood concentrations and possibly CCL2 concentrations might be related to the breed predisposition of the WHWT for CIPF and warrants further investigations. Highlights: Serum CXCL8 concentrations are elevated in healthy dogs from the WHWT breed. Serum CCL2 concentrations are elevated in healthy dogs from the WHWT and M breeds. No relevant interbreed differences exist for serum 5-HT concentrations regarding CIPF predisposition. Serum VEGF concentrations were below the kit detection limit in 89.3% of samples tested.